Understanding the Bond of Identification: An Investigation of its Correlates among Art Museum Members - Bhattacharya, C. B.; Rao, Hayagreeva; Glynn, Mary Ann (Journal of Marketing, 1995)
Identification is defined as the “perceived oneness with or belongingness to an organization” of which the person is a member. The authors propose that customers, in their role as members, identify with organizations. They use social identity theory to propose and test a model that relates members’ identification with the focal organization to (1) organizational and product characteristics, (2) members’ affiliation characteristics, and (3) members’ activity characteristics. Their empirical setting consists of the members of an art museum. Their survey findings show that members’ identification is positively related to perceived organizational prestige, donating activity, tenure of membership, visiting frequency, and confirmation of member expectations with the organization's services. However, members’ participation in similar organizations is negatively related to identification with the focal organization. The authors discuss how this study can be extended to other marketing contexts and how managers can use the notion of identification in implementing marketing strategies.